ANALISIS VEGETASI POHON PAKAN ORANGUTAN (Pongo pygmaeus Wrumbii) PADA TIGA HABITAT STASIUN RISET CABANG PANTI TAMAN NASIONAL GUNUNG PALUNG - ulandari, sari; Dewantara, Iswan; Kartikawati, Siti Masitoh (JURNAL HUTAN LESTARI, 2024)
Gunung Palung National Park is one of the habitats for Orangutans in West Kalimantan, and in this area, there is an Cabang Panti Research Station that focuses on conducting research on Orangutans, one of which is the type of feed. This study aims to examine the potential for species diversity and the similarity index of Orangutan forage tree species using the vegetation analysis method. The most common types of feed were found in frashwater swamp habitats and the least in alluvial habitats. The most common species found in three habtats, namely alluvial, freshwater swamp, lowland sandstone, was Popowia pisocarpa from the Annonaceae family, while the highest INP from the Polyalthia sumatrana species, which was 44.93% was feed for Orangutans at pole level in alluvial habitats. The results of the vegetation analysis of all growth levels for the diversity of tree species in the three habitats were classifield as moderate, the species distribution was evenly distributed and no species dominated. Three were similarity in the three habitats at tree level, while at the pole level only lowland sandstone habitat with alluvial.Keywords: Alluvial, Freshwater Swamp, Lowland Sandstone, Orangutan.AbstrakTaman Nasional Gunung Palung (TNGP) merupakan salah satu habitat Orangutan di Kalimantan Barat, dan kawasan ini terdapat Stasiun Riset Cabang Panti (SRCP) yang fokus melakukan penelitian Orangutan salah satunya adalah jenis pakan. Penelitian ini bertujuan untuk mengkaji potensi keanekaragaman jenis dan indeks kesamaan jenis pohon pakan Orangutan pada tiga habitat (alluvial, rawa air tawar, dan batu berpasir dataran rendah). Hasil analisis vegetasi pada ketiga habitat secara berurutan sebagai berikut INP tertinggi pada strata semai (P.pisocarpa 22,52%; S.platycarpa 13,67%; A.nitida 14,55%), strata pancang (P.pisocarpa 32,56%; K.laurina 16,41%; S.grande 22,95%), strata tiang (P.sumatrana 44,93%; P.rostrata 25,38%; P.pisocarpa 26,17%), dan strata pohon (S.Parvifolia 21,91%; S.platycarpa 30,85%; S.parvifolia 26,75%). Jenis pakan Orangutan yang ditemukan sebanyak 141 jenis dengan jenis pakan yang paling banyak ditemukan terdapat ada habitat rawa air tawar (107 jenis) dan yang paling sedikit pada habitat aluvial (86 jenis). Keanekaragaman jenis pohon pada tiga habitat untuk semua strata pertumbuhan tegolong sedang (H Ì…=1,3 "“ 1,9), penyebaran jenis tergolong merata dan tidak ada jenis yang mendominasi (C = 0 "“ 0,1). Terdapat kesamaan jenis pada tiga habitat untuk strata pohon (S = 50 "“ 86 %), tingkat tiang hanya habitat batu berpasir dataran rendah dengan aluvial (S = 87 %)Kata kunci: Aluvial, Rawa Air Tawar,batu Pasir dataran Rendah, Orangutan